Presenting Materials About Static Electricity with Video Based Demonstration: A Feasibility of Learning Media - Nyoman Adi Sudhira; I Made Citra Wibawa; I Made Suarjana (Universitas Pendidikan Ganesha, 2022)
This study is motivated by the finding that there is a lack of learning media in the learning process. This study aims to develop a valid and practical demonstration-based learning video media on static electricity in the fourth grade of elementary school. This study applies 4D modeling, namely (1) define or define; (2) design or design; (3) develop or development; and (4) disseminate or spread. This study involved two material experts, two media experts, two practitioners, and five students. This study uses qualitative and quantitative descriptive analysis methods. Data collection methods used are questionnaires or questionnaires and interviews. The average result of the validity of demonstration-based learning videos from material experts is 96.5% very good category, 96% of media experts in the very good category, 97.5% of practitioners in are very good category, and 96.8% of student responses are very good category. These results align with the study's aim to obtain learning media that pass the validity test. It was concluded that demonstration-based learning video media on static electricity were valid and suitable for use in learning activities in fourth-grade elementary school.